The relative contributions of pH, organic anions, and phosphatase to rhizosphere soil phosphorus mobilization and crop phosphorus uptake in maize/alfalfa polyculture - Sun, Baoru; Gao, Yingzhi; Wu, Xue; Ma, Huimin; Zheng, Congcong; Wang, Xinyu; Zhang, Hualiang; Li, Zhijian; Yang, Haijun (Plant and soil, 2020)
Aims To investigate the relative contributions of pH, organic anions concentration, and phosphatase activity to rhizosphere soil phosphorus availability and crop phosphorus uptake in polycultures. Methods A field experiment was conducted for three consecutive years in a split-plot design with main plots treated with two phosphorus levels and subplots treated with maize and alfalfa grown alone or intercropped. Results Intercropped maize and alfalfa had 0.35 and 0.24 units lower rhizosphere pH, 28% and 30% higher total organic anions (TOA) concentration, and 21% and 41% greater acid phosphatase activity than those in monoculture. These changes in root exudates induced significant increases in rhizosphere phosphorus concentration of intercropped maize and alfalfa by 21% and 41%, and pH and TOA had greatest contributions, respectively. Rhizosphere phosphorus mobilization facilitated phosphorus uptake of intercropped maize, but this facilitation was offset by phosphorus uptake reduction due to decreased crown root surface area. Lateral root volume enhancement accounted for phosphorus uptake improvement of intercropped alfalfa by 86.6%, while rhizosphere phosphorus mobilization only had a 0.2% contribution. Conclusions Rhizosphere pH and organic anions exhibit greater contributions than acid phosphatase activity in enhancing rhizosphere phosphorus availability. However, root surface area of maize and lateral root volume of alfalfa unveil greater influences on crop phosphorus uptake than rhizosphere pH and organic anions.